Marketing Orientation and its Application in the Lithuanian Mobile Telecommunications Market - Kurtinaitienė, Jolita (Ekonomika, 1999)
The article deals with the analysis of the widespread business orientations related to marketing. The theoretical framework allows formulating and presenting the supplemented definition of the marketing orientation. The paper aims to present the reader with the notion of marketing orientation, to investigate its implementation in the Lithuanian market of mobile communication.s and present the recommendations of the marketing orientation implementation in the Lithuanian firms. The market of the mobile communications was selected for the examination due to the presence of the antecedents favourable for the marketing orientation. The implementation of the marketing orientation in the firm is associated with the firm’s ability to innovate and find the best solutions for the satisfaction of the customer needs. Therefore, the activity of the mobile communications firms is analysed through the implementation of the new services. As the latest development in the mobile telecommunications market the prepaid service was chosen for the analysis. The study of the prepaid service introduction into the market of the Lithuanian mobile telecommunications is presented. The article is rounded up with the conclusions and recommendations concerning the implementation of the marketing orientation.